Polar Nighttime Chemistry Produces Intense Reactive Bromine Events. Issue 18 (23rd September 2018) - Simpson, W. R.; Frieß, U.; Thomas, J. L.; Lampel, J.; Platt, U.
Abstract: By examining the origin of airmasses that arrive at Utqiaġvik (formerly Barrow), Alaska, soon after polar sunrise (late January/early February), we identified periods when air arriving at Utqiaġvik had previously resided primarily at higher latitudes in near total darkness. Upon illumination, these airmasses produced high concentrations of reactive bromine, which was detected by differential optical absorption spectroscopy as bromine monoxide (BrO). These observations are consistent with nighttime production of a photolabile reactive bromine precursor (e.g., Br2 or BrCl). A large polar night source of photolabile reactive bromine precursors would contribute seed reactive bromine to daytime reactive bromine events and could export reactive halogens to lower latitudes and the free troposphere. Plain Language Summary: During the spring in the polar regions, unique halogen oxidizers dominate atmospheric chemistry, altering the fate of pollutants such as mercury. The sources of these oxidizers are not well understood, particularly during polar sunrise. Here we report the largest concentration ever detected of one of these species, bromine monoxide (BrO). We find these high concentrations occur when airmasses come out of the polar night, indicating a nocturnal source. Nocturnal production of reactive halogens could act as a seed source for subsequent reactive halogen photochemistry and could export reactive halogens from the polar night all winter. Key Points: At polar sunrise, we observe a surface mixing ratio of 90‐pmol/mol BrO, nearly doubling the prior peak observed in the Arctic Air that experienced little prior sunlight produced high BrO concentrations, consistent with a nocturnal source of photolabile precursors